Generation of Circular Optical Vortex Array. Issue 12 (23rd October 2017) - Ma, Haixiang; Li, Xinzhong; Tai, Yuping; Li, Hehe; Wang, Jingge; Tang, Miaomiao; Tang, Jie; Wang, Yishan; Nie, Zhaogang
Abstract: We report on a novel optical vortex array named circular optical vortex array, which is generated by the superposition of two concentric perfect optical vortices. The circular optical vortex array has a constant topological charge of +1 or −1, the number and sign of which are determined by the topological charges of the two perfect optical vortices. Moreover, the radius of the circular optical vortex array is easily adjusted by using the cone angle of an axicon. Furthermore, the circular optical vortex array and multiple circular optical vortex array can be rotated by changing the initial phase difference of the perfect optical vortices on demand. This work demonstrates a complex structured optical field, which is of significance for applications such as optical tweezers, micro‐particle manipulation, and optical imaging. Abstract : This work reports on a novel circular optical vortex array(COVA) generated by the superposition of two concentric perfect vortices. The COVA has a constant topological charge(TC) of ±1, the number and sign of which are determined by the TCs of the perfect vortices. The COVA and multiple COVA can be rotated by changing the initial phase difference. This work is of significance for applications such as optical tweezers and micro‐particle manipulation.